Unravelling nonclassical beam damage mechanisms in metal-organic frameworks by low-dose electron microscopy - Xiaoqiu Xu; Liwei Xia; Changlin Zheng; Yikuan Liu; Dongyang Yu; Jingjing Li; Shigui Zhong; Cuiyu Li; Huijun Song; Yunzhou Liu; Tulai Sun; Yonghe Li; et al. (Nature Communications)
Abstract Recent advances in direct electron detectors and low-dose imaging techniques have opened up captivating possibilities for real-space visualization of radiation-induced structural dynamics. This has significantly contributed to our understanding of electron-beam radiation damage in materials, serving as the foundation for modern electron microscopy. In light of these developments, the exploration of more precise and specific beam damage mechanisms, along with the development of associated descriptive models, has expanded the theoretical framework of radiation damage beyond classical mechanisms. We unravel, in this work, the nonclassical beam damage mechanisms of an open-framework material, i.e. UiO-66(Hf) metal-organic framework, by integrating low-dose electron microscopy and ab initio simulations of radiation induced structural dynamics. The physical origins of radiation damage phenomena, spanning across multiple scales including morphological, lattice, and molecular levels, have been unequivocally unveiled. Based on these observations, potential alternative mechanisms including reversible radiolysis and radiolysis-enhanced knock-on displacement are proposed, which account for their respective dynamic crystalline-to-amorphous interconversion and site-specific ligand knockout events occurring during continuous beam radiation. The current study propels the fundamental understanding of beam damage mechanisms from dynamic and correlated perspectives. Moreover, it fuels technical innovations, such as low-dose ultrafast electron microscopy, enabling imaging of beam-sensitive materials with uncompromised spatial resolution.